2016
DOI: 10.3390/ijms17122091
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of Cultured Lung Fibroblasts in Idiopathic Pulmonary Fibrosis: Meta-Analysis of Publically Available Microarray Datasets Reveals Repression of Inflammation and Immunity Pathways

Abstract: Heritable profibrotic differentiation of lung fibroblasts is a key mechanism of idiopathic pulmonary fibrosis (IPF). Its mechanisms are yet to be fully understood. In this study, individual data from four independent microarray studies comparing the transcriptome of fibroblasts cultured in vitro from normal (total n = 20) and IPF (total n = 20) human lung were compiled for meta-analysis following normalization to z-scores. One hundred and thirteen transcripts were upregulated and 115 were downregulated in IPF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
2
22
0
1
Order By: Relevance
“…Previous studies have demonstrated differences in the phenotypic responses between lung fibroblasts derived from control and IPF patients including a recent meta-analysis of microarray data showing repression of inflammation and immune pathways in IPF (35). We therefore decided to examine whether IL7AS and MIR3142HG have comparable functions during the IL1β-induced inflammatory response in IPF lung fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated differences in the phenotypic responses between lung fibroblasts derived from control and IPF patients including a recent meta-analysis of microarray data showing repression of inflammation and immune pathways in IPF (35). We therefore decided to examine whether IL7AS and MIR3142HG have comparable functions during the IL1β-induced inflammatory response in IPF lung fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Differentially expressed mRNAs and lncRNAs have been reported to be associated with development of lung fibrosis. Laurent et al explored the cultured lung fibroblast transcriptome of idiopathic pulmonary fibrosis; mRNAs encoding LIMS2, ASB1, and HHAT were upregulated and those encoding TRANK1, IFIT1, and SLC15A3 were downregulated [37]. Biswas et al found that, in cystic fibrosis, CTFR expression was regulated at the mRNA level [38].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this study suggested that alternative splicing of COL6A3 and POSTN, encoding extracellular matrix proteins collagen alpha‐3(VI) and periostin, might be involved in the pathogenesis of IPF (Nance et al, ). In a transcriptomic study on cultured lung fibroblasts from patients with IPF, downregulated genes were highly enriched in functional classes related to inflammation and immunity, while fibrogenic genes include connective tissue growth factor and serum response factor were upregulated (Plantier, Renaud, Respaud, Marchand‐Adam, & Crestani, ). However, the pathogenesis of IPF is not fully understood and may not appropriately represent the molecular details of silicosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a transcriptomic study on cultured lung fibroblasts from patients with IPF, downregulated genes were highly enriched in functional classes related to inflammation and immunity, while fibrogenic genes include connective tissue growth factor and FIGURE 6 Immunohistochemical analysis was conducted to examine the protein expressions of Ccl2 and Ccr2 in the mode and sham groups. Compared to the control, the protein expressions of Ccl2 and Ccr2 increased 1.86-and 1.54-fold in the mode group, respectively serum response factor were upregulated (Plantier, Renaud, Respaud, Marchand-Adam, & Crestani, 2016). However, the pathogenesis of IPF is not fully understood and may not appropriately represent the molecular details of silicosis.…”
Section: Verification Of Gene Expressions Via Reverse Transcriptionmentioning
confidence: 93%